Surgeon's comfort: The ergonomics of a robotic exoscope using a head-mounted display - Abramovic, Anto; Demetz, Matthias; Krigers, Aleksandrs; Bauer, Marlies; Lener, Sara; Pinggera, Daniel; Kerschbaumer, Johannes; Hartmann, Sebastian; Fritsch, Helga; Thomé, Claudius; Freyschlag, Christian F. (Brain & spine, 2022)
Conventional microscopes have certain limitations in terms of posture and ergonomics. Monitor-based exoscopes could solve this problem and thereby lead to less work-related sick leave for surgeons. The aim of this study was to assess the ergonomics, usability, and neurosurgeon's comfort of a novel three-dimensional head-mounted display-based exoscope in a standardized setting. 34 neurosurgeons participated in a workshop on the exoscope, which features a head-mounted display and a head gesture-triggered control panel. After completion of a custom-made 10-step microsurgical exercise, image quality and comfort were assessed using a questionnaire. The participants' posture during the exercise was analyzed using a video motion analysis software. 34 participants (median neurosurgical experience: 6 years) were included. The median time to complete the exercise was 12 ​min [IqR 9.4, 15.0]. Younger participants (p ​= ​0.005) and those with video game experience (p ​= ​0.03) had a significantly steeper learning curve. The median overall satisfaction was at 80% in general and 82% for image quality. The median upper body as well as the median head coronal displacement from the neutral axis were 0°. Participants with less microsurgical experience showed less head/body displacement during the exercise (p ​= ​0.01). Using the microsurgical training tool, we were able to depict a steep learning curve with a sufficient learnability of the most relevant commands. The exoscope excelled in usability, image quality as well as in ergonomic and favorable posture and could thus become an alternative to conventional microscopes due to the potentially elevated surgeons' comfort. •Overall, the participants were satisfied with the exoscope usability (80%) and image quality (82%).•The custom-made microsurgical exercise tool is an efficient tool for assessment of the participant's performance with the head-mounted display-based exoscope.•Younger participants with video games experience showed a steeper learning curve for the performance of the microsurgical training tool.•After performing theexercise, 88% of the participants felt safe to use the HMD-based exoscope in the OR.